2020
DOI: 10.1002/mmce.22447
|View full text |Cite
|
Sign up to set email alerts
|

A new structure of microwave‐driven UV lamp

Abstract: Microwave‐driven electrodeless UV lamps are widely used in industry. However, the ultraviolet light intensity of the traditional UV lamps is non‐uniform. In this article, a novel microwave‐driven UV lamp structure for underwater sterilization is developed, which equalizes the UV light intensity of each lamp at different positions. Based on the electromagnetic theory and the Drude model, finite difference time domain algorithm is adopted to obtain the dimensions of this new structure. An experimental system is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the Drude model is a classical physical model that simplifies the conductive behavior of a plasma, making it an efficient choice for designing electrodeless plasma lamps. Despite its simplifications, it has been widely used in plasma physics research and has shown relatively accurate results in specific scenarios [25][26][27]. Compared to other models like particle dynamics models and fluid models, it strikes a balance between simplicity and accuracy.…”
Section: Dimension Optimizationmentioning
confidence: 99%
“…Furthermore, the Drude model is a classical physical model that simplifies the conductive behavior of a plasma, making it an efficient choice for designing electrodeless plasma lamps. Despite its simplifications, it has been widely used in plasma physics research and has shown relatively accurate results in specific scenarios [25][26][27]. Compared to other models like particle dynamics models and fluid models, it strikes a balance between simplicity and accuracy.…”
Section: Dimension Optimizationmentioning
confidence: 99%
“…For designing a novel MW‐APPJ, it is necessary to analyze | S 11 | and electric field strength. [ 31 ] In addition, | S 11 | represents the reflection coefficient of microwave power, which is the ratio of the reflected power to the incident power. Generally, the optimization parameter of |S 11 | is less than −10 dB, which means that more than 90% of microwave energy is absorbed by the plasma.…”
Section: Numerical Modelmentioning
confidence: 99%